Comparison of LLW Disposal Facilities at Major Department of Energy Sites. Issue 1 (17th December 2015) - Rustick, Joseph H.; Kosson, David S.; Krahn, Steven L.; Ryan, Michael T.; Benson, Craig H.; Clarke, James H.
Abstract : Near surface disposal facility design and management are examined and compared using a systems approach that defines facility performance as a function of three components (or subsystems): the disposal facility design (cover systems and bottom liners); the properties of the waste (waste composition, waste form and waste package); and the site‐specific environmental features (climate, geology, and hydrology). We report an evaluation of five DOE near surface disposal facility case studies, selected to provide a "representative" sample that included disposal sites with a range of waste and environmental characteristics across the DOE. The facilities selected were the Savannah River E‐Area Engineered Trenches, Hanford Integrated Disposal Facility, Idaho Radioactive Waste Management Complex, Oak Ridge Environmental Management Waste Management Facility, and Nevada National Security Site Area 5. ©2015 Wiley Periodicals, Inc.